Development and validation of fluorescence live-cell imaging approaches to study flavivirus infection kinetics in animal cells - Arias Arias, Jorge Luis (2021)
The genus Flavivirus in the family Flaviviridae comprises many clinically important viruses, such as dengue virus (DENV), Zika virus (ZIKV), and yellow fever virus (YFV). The quest for therapeutic targets to combat flavivirus infections requires a better understanding of the kinetics of the virus-cell interplay during infections with wild-type viral strains. Nevertheless, this is hindered by limitations of the current cell-based systems for monitoring flavivirus infection by live-cell imaging. The present dissertation describes the development and validation of fluorescence-activatable sensors to detect the activity of flavivirus NS2B-NS3 serine proteases in living cells. The system consists of green fluorescent protein (GFP)-based reporters that become fluorescent upon cleavage by recombinant DENV-2/ZIKV proteases in vitro. A version of this sensor containing the flavivirus internal NS3 cleavage site linker (AAQRRGRIG) reported the highest fluorescence activation in stably transduced mammalian cells upon DENV-2/ZIKV infection. The onset of fluorescence correlated with viral protease activity. Moreover, a far-red version of this flavivirus sensor presented the best signal-to-noise ratio in a fluorescent Dulbecco’s plaque assay, leading to the construction of a multireporter platform combining the flavivirus sensor with DNA fluorescent dyes for the detection of virus-induced chromatin condensation and cell death (cytophatic effect labeling). This enabled studies of viral plaque formation with a single-cell resolution. This cytopathic effect labeling approach was conceptualized and validated during the present work. Finally, the application of the multireporter platform also enabled the study of kinetics of infection and cytophatic effect induction by DENV-2, ZIKV, and YFV in cell-subpopulations. We anticipate that future studies of viral infection kinetics with our reporter systems will enable basic investigations of virus-host cell interactions and will also facilitate the screening of antiviral drugs to manage flavivirus infections.